Psychological factors influencing the formation of therapeutic cooperation in pulmonary tuberculosis patients undergoing in-patient treatment - N. V. Zolotova; V. V. Streltsov; G. V. Baranova; N. Yu. Kharitonova; T. R. Bagdasaryan (Туберкулез и болезни лёгких)
The objective of the study: the comparative study of psychological characteristics of pulmonary tuberculosis patients with different levels of therapeutic cooperation during in-patient treatment.Subjects and nethods. 318 pulmonary tuberculosis patients aged 18-60 years old were enrolled in the study; they all underwent in-patient treatment in Central Tuberculosis Research Institute in 2017-2019, of them 195 (61.3%) were women and 123 (38.7%) were men. In all patients, the level of therapeutic cooperation was studied using the specially designed questionnaire; psychological characteristics were assessed using certain psychodiagnostic methods.Results. It was found that the proportion of patients with a high level of therapeutic cooperation (44.3% of cases) significantly prevailed versus patients with low (29.6% of cases) (Pearson χ2 = 9.4; p < 0.01) and moderate level of cooperation (26.1% of cases) (Pearson χ2 = 15.02; p < 0.001). A comparative study of the psychological characteristics of pulmonary tuberculosis patients demonstrating different levels of therapeutic cooperation allowed identifying psychological prognostic parameters of therapeutic cooperation, the main of which were the severity of suspicion, negative affective states (irritability, aggressiveness), distrustful-skeptical style of interaction, confrontation with others, as well as the level of quality life, primarily the emotional and social aspects of functioning. The detected psychological differences are considered as targets of psychological work focused on the formation of appropriate therapeutic cooperation during in-patient treatment.